Heterojunction between Al2O3 and SnO2 thin films for application in transparent FET - Boratto, Miguel Henrique [UNESP]; Andrade Scalvi, Luis Vicente de [UNESP]; Barbosa Maciel, Jorge Luiz [UNESP]; Saeki, Margarida Juri [UNESP]; Floriano, Emerson Aparecido [UNESP] (Univ Fed Sao Carlos, Dept Engenharia Materials, 2014)
Alternative materials for use in electronic devices have grown interest in the past recent years. In this paper, the heterojunction SnO2/Al2O3 is tested concerning its use as a transparent insulating layer for use in FETs. The alumina layer is obtained by thermal annealing of metallic Al layer, deposited by resistive evaporation technique. Combination of undoped SnO2, deposited by sol-gel-dip-coating technique, and Al thermally annealed in O-2-rich atmosphere, leads to fair insulation when the number of aluminum oxide layers is 4, with 0.3% of the current lost through the gate terminal as leakage current. This insulation is not obtained for devices with alumina layer treated for long time, under room atmosphere, due to degradation of the insulating film and interfusion with the conduction channel even using Sb-doped SnO2. The annealing of Al deposited on soda-lime glass substrate leads also to the formation of a Si layer, crystallized at Substrate/Al2O3 interface. The conclusion is that for an efficient insulation the thermal annealing must be short and then, O-2-rich atmospheres are preferred.
Keywords: Aluminum oxide; Heterojunction; Tin dioxide; FET